EFISIENSI BMT SEBAGAI NADZIR DALAM PENGELOLAAN WAKAF UANG - azmi, muhammad ulul (Mu'amalatuna: Jurnal Ekonomi Syariah, 2019)
Waqf is one of the Islamic economics instruments that is very important in the economisc empowerment of Muslims. So far waqf is only synonymous with Islamic charity in the form of fixed assets, such as land and buildings, but now the development of waqf is increasingly widespread with the existence of cash waqf. Cash waqf makes it easy to mobilize funds from the community through cash waqf certificates that can be made in various fractions according to the segment of the community, so that everyone can be a wakif. However, management of waqf has not been optimally empowered, so measurement of efficiency performance is expected to help in optimizing the potential of cash waqf management.This study aims to analyze the level of efficiency of cash waqf management institutions from several BMTs listed as Nadzir by BWI during the period 2012-2017. Two Stage DEA is used to measure the efficiency level of cash waqf management institutions and the factors that influence the level of efficiency. The collected funds, total labor and labor costs (X3) are input variables. The distribution of managed funds and profits are output variables.